2020
DOI: 10.3390/biom10020319
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Role of Serum and Urine Biomarkers (PLA2R and THSD7A) in Diagnosis, Monitoring and Prognostication of Primary Membranous Glomerulonephritis

Abstract: Differentiating primary and secondary membranous glomerulonephritis (MGN) using biomarkers for MGN is essential in patients’ diagnosis, treatment and follow-up. Although biopsy has been the primary tool in making the diagnosis, not all patients can withstand it due to its invasive nature, and it cannot be used to monitor treatment. Hence, there is the need for less invasive or even non-invasive biomarkers for effective diagnosis, treatment monitoring and prognostication. This study aimed at providing an altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Similar to the anti-PLA2R antibody, the anti-THSD7A antibody is mostly detected in IMN; however, it cannot completely distinguish IMN from SMN. Maifata et al (30) detected the serum anti-THSD7A antibody in four patients with IMN (4/47, 8.5%) and in two patients with SMN (2/22, 9.1%). In addition, studies have shown that the anti-THSD7A antibodies levels are associated with the treatment response and disease activity (46).…”
Section: Thsd7amentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the anti-PLA2R antibody, the anti-THSD7A antibody is mostly detected in IMN; however, it cannot completely distinguish IMN from SMN. Maifata et al (30) detected the serum anti-THSD7A antibody in four patients with IMN (4/47, 8.5%) and in two patients with SMN (2/22, 9.1%). In addition, studies have shown that the anti-THSD7A antibodies levels are associated with the treatment response and disease activity (46).…”
Section: Thsd7amentioning
confidence: 99%
“…Many studies have shown that PLA2R is more common in IMN than in SMN (26)(27)(28)(29)(30)(31), suggesting that PLA2R has certain clinical value for distinguishing between the two types. However, it has also been detected in SMN (26)(27)(28)(29)(30)(31), especially in hepatitis, sarcoidosis, and tumor-related SMN. Larsen et al (31) detected PLA2R1 in 80 cases of SMN renal tissues by indirect immunofluorescence.…”
Section: Pla2rmentioning
confidence: 99%
“…Due to its autoimmune nature, these MN cases are defined as primary MN 1 . The identification of PLA2R and THSD7A auto‐antibodies has contributed to the understanding of MN pathogenesis and both have been used as diagnostic and prognostic biomarkers in MN 7,8 …”
Section: Figurementioning
confidence: 99%
“…Nevertheless, reduction in proteinuria is related to achieving remission in primary MGN (6,7). In addition, studies were conducted on the same patients to determine the prognosis using M-type phospholipase A2 receptors (M-PLA2R) and Thrombospondin domain-containing type 7 A (THSD7A) demonstrated a direct relationship with proteinuria (8). In this study, we predict prognostic risk factors for primary MGN patients for effective intervention.…”
Section: Introductionmentioning
confidence: 99%